Constitutive material model for the design and virtual testing of pressure vessel service equipment manufactured from thermoplastic fiber-reinforced polymer composites. (October 2021) - Sergeichev, Ivan; Fedulov, Boris; Fedorenko, Alexey; Zershchikov, Konstantin; Lomakin, Evgeny; Akhatov, Iskander
Abstract: In this study the short-fiber thermoplastic polymer composite is proposed to produce a pressure vessel service equipment used for the transportation of chemicals and dangerous goods. Mechanical tests show nonlinear response of this composite, including initial elastic stage of loading. To address the stress analysis problem, the constitutive material model was proposed and calibrated to describe the nonlinear elastic and elastoplastic behavior of the material with advantage of stiffness dependence on the realized stress state. Standard tension, compression and shear tests are sufficient for the determination of the model parameters in the simplest case, while the model accuracy increases with additional biaxial or triaxial stress state test data. A three-point bending test was proposed as a case of combined loading for model verification. The model was implemented into ABAQUS finite element solver via a user material subroutine for practical usage. The applicability of the model was demonstrated for the stress analysis of typical shut-off valve made of short-fiber composite. The variety of the stress states, which are typical for considered structure, was investigated in order to evaluate what types of experiments are required to improve the accuracy of the model. Highlights: Short-fiber thermoplastic composites show nonlinear mechanical response. The proposed elastoplastic model is stress state-dependent. Only minimum tests are required for calibration, further improvement is possible. Three-point bending test is useful for model validation. Application to the industrial case is investigated.